POTENSI PRODUKSI BIOHIDROGEN DARI LIMBAH BIOMASSA PADA PROSES PENCERNAAN ANAEROBIK - Bintang Sipartogi Panjaitan; Linda Lestari; Radite Praeko Agus Setiawan; Armansyah Halomoan Tambunan (AGROINTEK, 2021)
The sustainability of hydrogen as an energy carrier depends on the production process and the source of raw materials. The choice of substrate in anaerobic digestion process plays an important role to maximize biohydrogen production because it depends on its availability and the composition of substrate. The purpose of this study is to design and construct a prototype reactor for biohydrogen production and to determine the potential of H2 gas production from anaerobic digestion process. This study uses an experimental research method with three operating temperature variations in the reactor, at the range of thermophilic temperatures, i.e. 55°C, 60°C, and 65°C. The substrate used was POME and cow dung, and the process was conducted in 24 hours which is assumed to be the stage of non-methanogenic within the anaerobic process. From this research, the prototype of continuous stirred tank reactor (CSTR) in batch system was made from acrylic, with a capacity of 6 liters biomass waste. Using the reactor, total biohydrogen gas produced during 24 hours process with cow manure as substrate was 0,0932 gram at 55°C; 0,0307 gram at 60°C and 0,0797 gram at 65°C. While, biohydrogen production using POME as substrate was 0,0645 gram at 55°C; 0,1708 gram at 60°C, and 0,0636 gram at 65°C. These results indicate the potentiality of POME and cow manure to produce biohydrogen gas during anaerobic digestion process.